White Gold: The Commercialisation of Rice Farming in the Lower Mekong Basin 2020
DOI: 10.1007/978-981-15-0998-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Organizations in Ubon Ratchathani Province

Abstract: Notwithstanding the rapid growth of commercial agriculture in Thailand over the past half century, farmer organizations and community enterprises have been a common and distinctive feature of the rural economy and have been strongly supported by government policies, especially with the promotion of the “sufficiency economy”. While informal cooperation has been a traditional part of village life, the government has consistently promoted more formal organizational arrangements for farmers, alongside policies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…The motives for adoption of organic farming include pursuing higher income, preventing health issues by reducing the use of synthetic pesticides, and conservation of environments, which is expected to contribute to sustainable development of the agriculture sector ( Ullah et al., 2015 ; Kramol et al., 2020 ). Application of biofertilizers to soil helps keep the plants healthy and gradually improves biodiversity on farmland ( Yanakittkul and Aungvaravong, 2020 ; Sapbamrer and Thammachai, 2021 ).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…The motives for adoption of organic farming include pursuing higher income, preventing health issues by reducing the use of synthetic pesticides, and conservation of environments, which is expected to contribute to sustainable development of the agriculture sector ( Ullah et al., 2015 ; Kramol et al., 2020 ). Application of biofertilizers to soil helps keep the plants healthy and gradually improves biodiversity on farmland ( Yanakittkul and Aungvaravong, 2020 ; Sapbamrer and Thammachai, 2021 ).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…(2017) revealed that experienced rubber farmers in Thailand preferred to sell their produce through farmer groups for gaining bargaining power, fetching higher output prices, and obtaining government support. Economic incentives can drive farmers to participate in farmer groups ( Sumarsono and Widjajanto, 2017 ; Kramol et al., 2020 ; Yanakittkul and Aungvaravong, 2020 ).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations